Relationship Between Socio-Economic Factors of Pad Rice Farmers With Implementation of Integrated Crop Management (ptt) Programs In Empelu Village, Tanah Sepenggal District bungo District - Amran Amran (Baselang, 2022)
This research was conducted in Empelu Hamlet, Tanah Sepenggal District, Bungo Regency with the consideration that in the hamlet there were field agricultural extension agents with the Integrated Crop Management (PTT) program and as a food production center in Tanah Sepenggal District, Bungo Regency. The time of the research was carried out for 2 months. namely from 20 June 2021 to 20 August 2021. The purpose of this study was to determine the relationship between socio-economic factors of farmers (Level of Education, Age of Farmers, Land Area, Farming Experience and Income of farmers) with the implementation of the Integrated Crop Management (PTT) program. in the research area and to find out the problems encountered in the implementation of Integrated Plant Management (PTT) in the research area. The method used to analyze the data is a quantitative descriptive method with interview techniques with farmers based on a questionnaire containing a series of questions regarding the problems encountered in paddy rice farming and efforts to overcome them. The results of this study showed that the age factor, farming experience and land area had no relationship with the Integrated Crop Management Program (PTT) for lowland rice farming, but the level of education and total income had a relationship with the Integrated Plant Management Program (PTT) in the study area. The problems faced by the sample farmers were plant pest disturbances, bad weather and irrigation which greatly affected the lowland rice farming because it could reduce the quality and quantity of the sample farmers' lowland rice plants. Meanwhile, to deal with weather and irrigation, farmers work in mutual cooperation